Penyuluhan Kesehatan Pentingnya Imunisasi Dasar Lengkap di Puskesmas Wek 1 Padangsidimpuan - Pane, Mustika Dewi; Rambe, Muhammad Arsyad Elfiqah (Jurnal Pengabdian Masyarakat Aufa (JPMA), 2023)
The low coverage of complete basic immunization is still a very difficult problem to face. Based on research conducted by Nurhikmah in 2017, knowledge and motivation factors are closely related to compliance. Knowledge is the dominant factor in compliance with immunization, so that the wek 3 sub-district area of padangsidimpuan city deserves to receive education about the importance of complete basic immunization. The desired method is the provision of materials carried out in the working area of the public health center, padangsidimpuan city. From the results of this counseling, there is an increase in knowledge and understanding. It is hoped that this training activity can be carried out in all work areas of the health center and government support is very important as information media so that it can be carried out continuously by posyandu cadres.